Shari'ah governance in Islamic banks - Zulkifli Hasan (Edinburgh guides to Islamic finance, 2012)
Shari'ah governance has a profound influence on the day-to-day practice of Islamic Financial Institutions (IFIs) and each jurisdiction has adopted a different approach to developing a governance framework. With examples, case studies and practical discussions, this title reviews these pluralistic approaches and identifies best practice